2020
DOI: 10.1097/gox.0000000000002739
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with Foam-mediated External Suction on Flap Microvasculature and Perfusion in a Rodent Model

Abstract: Background: Foam-mediated external suction (FMES) has previously shown to improve tissue microcirculation. We hypothesized that preconditioning fasciocutaneous perforator flaps with FMES would augment perfusion and demonstrate greater capillary recruitment. Methods: Gluteal perforator flaps were designed on sixteen 400 g rats. Continuous FMES at −125 mm Hg was applied on one side (intervention) to precondition tissue for 5 days, with the contralateral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…They found a 2-fold increase in mean vessel volume and a 30% increase in absolute intensity when evaluated with indocyanine green angiography in preconditioned flaps. 14 Other authors have reported similar findings of increased vascularity and improved flap survival in animal models when treated with external negative pressure. [15][16][17][18][19] It is unclear what the optimal treatment conditions and duration of therapy are at the present time.…”
Section: Current Evidencementioning
confidence: 59%
See 3 more Smart Citations
“…They found a 2-fold increase in mean vessel volume and a 30% increase in absolute intensity when evaluated with indocyanine green angiography in preconditioned flaps. 14 Other authors have reported similar findings of increased vascularity and improved flap survival in animal models when treated with external negative pressure. [15][16][17][18][19] It is unclear what the optimal treatment conditions and duration of therapy are at the present time.…”
Section: Current Evidencementioning
confidence: 59%
“…The most common pressure setting reported is −125 mm Hg, and both continuous and intermittent suction settings have been utilized. 12–16 The report time period of treatment also varies, with the most common length of treatment being 5–7 days before intervention. 12–16 We present our initial experience using ENPD in free ALT flap reconstruction of upper extremity defects.…”
Section: Current Evidencementioning
confidence: 99%
See 2 more Smart Citations